(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Corpus linguistics is now known to expand our knowledge of a variety of phenomena in linguistics and literature. However, few studies have been undertaken to test its effects on literature studies. The field of study that analyzes literary texts by using corpus linguistic techniques is called corpus stylistics. It extracts literary meaning by using corpora. This paper sets out to explore three corpus-based techniques: concordances, frequency lists, collocate lists in the analysis of literary works. The basic question is whether these techniques is helpful to gain more objective and perceptive knowledge of literary texts. Seven English-translated stories of Utkir Hoshimov (The butterfly and the tank, Disturbed dream, Why, Happiness, Solar scales, Three kinds of people, The last victim of the war ) are laid to corpus linguistic analysis. Due to the corpus-based techniques large amounts of literary data are analyzable. Otherwise, the data is not more than several lines of poetry or short extracts of narrative.